2012
DOI: 10.1210/jc.2012-1235
|View full text |Cite
|
Sign up to set email alerts
|

Drawings Reflect a New Dimension of the Psychological Impact of Long-Term Remission of Cushing's Syndrome

Abstract: Drawings reflect a new dimension of the psychological impact of long-term remission of Cushing's syndrome because drawings do not share common properties with parameters of QoL or illness perceptions, but do represent the clinical severity of the disease. The assessment of drawings may enable doctors to appreciate the perceptions of patients with long-term remission of Cushing's syndrome and will lead the way in dispelling idiosyncratic beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 30 publications
5
35
1
1
Order By: Relevance
“…In the hysterectomy group, the score dropped from 5.9 to 2.6. These results are consistent with results from other drawing studies in that the size of the drawn organs is reduced after the upsetting event has taken place [21,[29][30][31][32][33]. The intraclass correlation coefficient between G. S. and L. R. on Drawing 1 and Drawing 2 was 0.82 and 0.66, respectively.…”
Section: Drawings (Figure 3)supporting
confidence: 91%
See 2 more Smart Citations
“…In the hysterectomy group, the score dropped from 5.9 to 2.6. These results are consistent with results from other drawing studies in that the size of the drawn organs is reduced after the upsetting event has taken place [21,[29][30][31][32][33]. The intraclass correlation coefficient between G. S. and L. R. on Drawing 1 and Drawing 2 was 0.82 and 0.66, respectively.…”
Section: Drawings (Figure 3)supporting
confidence: 91%
“…A relatively new method to assess illness perceptions is through patients' drawings of affected organ(s) [21,[28][29][30][31][32][33]. It has the advantage of circumventing possible social desirability issues and provides a unique and value free illustration of a person's illness perceptions [31]. All women were asked to retrospectively draw images of her uterus and pelvic area during the event (Drawing 1) and at the time of returning the questionnaires (Drawing 2).…”
Section: Drawingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawing test has successfully been used in patients after long-term remission of Cushing's syndrome (11), and other chronic conditions such as myocardial infarction (10), heart failure (9), headache (12), postpartum hemorrhage (13), vestibular schwannoma (14), and systemic lupus erythematosus (15). Drawings appeared to reflect a new dimension of the psychological impact of long-term remission of Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Drawings appeared to reflect a new dimension of the psychological impact of long-term remission of Cushing's syndrome. Drawings and scores on an Illness Perception Questionnaire (IPQ) showed marginal correlations (11). The other studies using the drawing test in non-endocrine conditions showed that drawings illustrate the functional and psychological status of the patient.…”
Section: Introductionmentioning
confidence: 99%